DIGITALIZATION OF THE COURT SYSTEM OF THE REPUBLIC OF UZBEKISTAN - Pulatovich, Komolov Dilshod (Journal of Learning on History and Social Sciences, 2024)
Objective: This article explores the digitalization of the judicial system in the Republic of Uzbekistan, focusing on its stages, the enhancement of judges' IT knowledge, and the integration of information technologies to improve judicial transparency and efficiency. Methods: The study employs widely accepted research methods including objectivity, historical analysis, comparative-logical analysis, and chronological sequence principles to examine the ongoing transformation. Results: The digitization process, exemplified by the "Adolat" information systems complex, has significantly improved judicial operations. Through this system, various stakeholders, including state authorities, local government bodies, and lawyers, can submit and monitor claims electronically, enabling online court proceedings and automatic generation of court documents. This process enhances the transparency, speed, and accessibility of the judicial system. Novelty: The article highlights the innovative use of digital technologies in judge selection, training, and appointment, ensuring impartiality and promoting transparency in judicial evaluations. The integration of information systems between state bodies and the judiciary has led to increased efficiency in the justice system. The findings underscore the transformative potential of digitalization in meeting the demands of modern justice, improving public satisfaction, and ensuring the independence and fairness of the judicial process.